Algeria’s Fintech Landscape: Challenges, Opportunities, and Current Reality (مجلة الواحات للبحوث والدراسات, 2026)
Implementing Fintech techniques into the economy has become increasingly crucial, offering unparalleled opportunities for growth, efficiency, and inclusivity. Therefore, this research seeks to investigate the opportunities of applying Fintech techniques in the real economy, with a specific focus on the Algerian context, examining the current state of Fintech adoption in Algeria, and identifying its main challenges; also, discussing the relevant global best practices. Based on descriptive and analytical approaches. The study concludes that the application of Fintech can lead to the improvement of the efficiency and speed of financial and banking operations, saving time and effort for customers and financial institutions. Regarding Algeria, the application of financial technology is still in the early stages of implementation and adoption, which argues more attention to the actual application of all measures that help to accelerate Fintech techniques implementations to speed up the operations of financial inclusion in Algeria.